If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 23 = 11x + -2 Reorder the terms: 23 + 6x = 11x + -2 Reorder the terms: 23 + 6x = -2 + 11x Solving 23 + 6x = -2 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 23 + 6x + -11x = -2 + 11x + -11x Combine like terms: 6x + -11x = -5x 23 + -5x = -2 + 11x + -11x Combine like terms: 11x + -11x = 0 23 + -5x = -2 + 0 23 + -5x = -2 Add '-23' to each side of the equation. 23 + -23 + -5x = -2 + -23 Combine like terms: 23 + -23 = 0 0 + -5x = -2 + -23 -5x = -2 + -23 Combine like terms: -2 + -23 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| 2(2x-5)=18 | | 11x+2=5x+56 | | 5x+9-2x+4+7y= | | 4x+33=3x+24 | | .167(z+3)=-.5(z+2) | | (y-8)-(y+8)=6y | | 2x/15=4/5 | | (x+3)(sx+5)=7 | | 34-4x=10-10x | | y^2+5xy=3x^3 | | v+.83v-.17=.375(v+.67) | | 1/14(196x-98)=156 | | 7v-28=-7v | | 2(8+2x)=96 | | 3n^2-13n-63=-7 | | 12=5z+12 | | 9m+5=9m+5 | | -(21+16y)-7+53y= | | x+20x+30=0 | | 1x+20x+30x=0 | | 3x-6/-6=0 | | 3t-14=34 | | -1(x+3)=-5 | | 3t+14=34 | | 78+22m=15m | | 5x+12=12-10x | | 5=x^2-5x-9 | | (x-1)*(x-1)*(x-1)-4(x+1)*(x+1)=x*x(x-7) | | 5+8r=-2+7r | | x^3-9x=x^2+9 | | f(x)=3x^3+19x^2-14x | | 9a+6= |